Comparison of Clinical and Radiological Parameters with Two Different Surgical Methods for Anterior Cruciate Ligament Reconstruction - Çiloğlu, Osman; Çiçek, Hakan; Yılmaz, Ahmet; Özalay, Metin; Söker, Gökhan; Leblebici, Berrin (The Journal of Knee Surgery, 2020)
This study compared the clinical and radiological findings of nonanatomic transtibial (TT) technique with intraspongious fixation and anatomical anteromedial portal (AMP) technique with extracortical button implant in anterior cruciate ligament (ACL) reconstruction. A total of 54 patients with isolated ACL rupture were included in this prospective study. The patients who had the intraspongious fixation by nonanatomical TT technique were allocated to Group 1 (n = 27). The patients with extracortical fixation by anatomical AMP technique were placed in Group 2 (n = 27). The clinical scores of the patients were evaluated with the International Knee Documentation Committee Evaluation Form, Tegner activity score, and Lysholm II Functional Scoring. The tibial and femoral tunnels were evaluated with three-dimensional computed tomography. The kinematic examinations were performed with a Biodex System 3 Pro isokinetic dynamometer. There was no significant difference between the groups in terms of demographic data (p > 0.05). The postoperative clinical scores improved significantly in both the groups compared with the preoperative levels (p = 0.001), but there was no significant difference in the postoperative clinical scores between the groups (p > 0.05). In the extension and flexion of 60 to 180 degrees/s, the peak torque and the peak torque/body weight values of the repaired knee to intact knee ratios showed significant differences in favor of Group 2 (p = 0.001). In both the groups, no significant difference was found between the mean extent of the tunnel enlargement (p > 0.05). The mean tunnel height was significantly greater in Group 1 (45% ± 9.86 vs. 34.11% ± 10.0%) (p = 0.001). When the localization of the tunnel enlargements (proximal-middle-distal) was examined, a significant difference was found between the groups (p = 0.001). Although the AMP technique, which is a more anatomic reconstruction, had an advantage with regard to tunnel enlargement and the isokinetic muscle studies, there was no difference between the two techniques in terms of the clinical results.
Keywords: anterior cruciate ligament reconstruction; isokinetic muscle strength; tunnel placement; tunnel enlargement